Redefining Ngurek Bali: Analysis of Audience Perception in The Cyber World - Addina Isaputri; Lambok Hermanto Sihombing (Jurnal Penelitian Agama Hindu, 2022)
The problem in this research is the public response against the Balinese ngurek tradition. This research discusses the reinterpretation of a Hindu religious ritual in Bali, namely the ngurek ritual or often referred to as ngunying. This religious ritual is quite unique and extreme so it has many meanings. This type of research is a qualitative research with reference to Stuart Hall's encoding-decoding theory. This data collection was obtained through youtube with comments and also the results of interviews with one of the informants. Data analysis with data reduction, data presentation and conclusion drawing. The results of this study indicate that the topics that appear in the comments are not limited to traditional rituals. The material also involves involvement and controversy between the religious rituals of ngurek and Hindu rituals in Bali simultaneously. The new thing that can be known is that the ngurek tradition is an ancient Balinese custom, where a spirit invitation ceremony is held. The spirits are asked to enter into the designated body and be a sign that the invited spirit will be present. The ngurek tradition is also believed to invite Ida Bhatara and Rereancang (his soldiers) to receive offerings during the ceremony.